Development of bioclogging methods for soils - Lim, Jane Hui Qi. (2011)
Abstract Advancement in biotechnology and engineering have gave rise to many new developments in the industries. There has been a search for a more cost-efficient and environmental-friendly construction material which can be used in geosynthetic clay liners for example. In order to produce such a construction material, this project aims to adopt biological methods to improve the physical properties of soil such as reduction in permeability. In this project, the technique of bioclogging is explored where sand is treated with bacteria in a bid to decrease the permeability of sand to enhance its ability to prevent leakages. Urease-producing bacteria and iron-reducing bacteria are two types of bacteria used in this project to induce bioclogging in sand. The urease-producing bacteria are added to the sand by spraying, while the iron-reducing bacteria are mixed with the sand and placed in an anaerobic condition. Experiments were conducted to investigate the permeability of the sand after the bacterial treatments. Results obtained from permeability test conducted using a triaxial cell indicated that bioclogging is successful as the permeability of sand has decreased from 10-4 m/s to 10-8 m/s. However, samples treated with iron-reducing bacteria have higher permeability values than those treated with urease-producing bacteria only. Calcium and iron determination tests were conducted to assess the amount of carbonate and ferrous hydroxide precipitation which contributes to the clogging of particles. Scanning electron microscopic images also show the presence of bacteria in all the samples tested. Hence, we can conclude that bioclogging is a technique to retain bacteria in sand where the bacterial activity will catalyse the precipitation of solids to clog the pores of sand in order to produce an impermeable layer capable to prevent migration of liquids.